Uluslararası Deniz Hukuku Mahkemesinin İhtiyati Tedbir Yetkisi - SARIBEYOĞLU SKALAR, MELTEM (My University, 2019)
Uluslararası Deniz Hukuku Mahkemesi 1982 Birleşmiş Milletler Deniz Hukuku Sözleşmesi ile kurulmuş bir yargı organıdır. Mahkeme kurulduğundan itibaren birçok ihtiyati tedbir talebini karara bağlamıştır. Mahkemenin ihtiyati tedbir yetkisinin esası BMDHS’nin 290. maddesine dayanmaktadır. Bunun yanı sıra, BMDHS, Mahkeme’ye olağanüstü ihtiyati tedbir yetkisi vermiştir. Bu yetkisi ile Mahkeme uyuşmazlığın görüleceği yargı yeri olmamasına rağmen ihtiyati tedbire karar verebilir. Bunlara ek olarak başka sözleşmelerle de Mahkemeye ihtiyati tedbir yetkisi verilmiştir. Ve yine sözleşmede mahkemenin hükmetmesine gerek olmayan kendiliğinden doğan ihtiyati tedbirler konulmuştur. Bu kapsam da makalede öncelikle Mahkemenin BMDHS’den ve diğer Sözleşmelerden doğan ihtiyati tedbir yetkisi belirlenecek, resen doğan ihtiyati tedbirlerden söz edilip ihtiyati tedbirlerin hükmedilmesi, değiştirilmesi ve ortadan kaldırılması incelenecektir. Böylelikle UDHM’nin ihtiyati tedbir yetkisine ilişkin genel bir çerçeve ortaya konulacaktır.1

The International Tribunal for the Law of the Sea is an international permanent judicial organ established in accordance with the United Nations Convention on the Law of the Sea. Many cases have been decided on provisional measures by the Tribunal since its establishment. The legal basis of the ITLOS’s competence to decide on provisional measures is regulated at the Article 290 of UNCLOS. In addition to this, UNCLOS has given to ITLOS an extraordinary jurisdiction for provisional measures. Even if ITLOS sometimes is not a judicial body to solve a dispute on the merits, a provisional measure could be prescribed on this dispute by the ITLOS. And also the jurisdiction for provisional measure has been given to ITLOS by some other agreements. Besides, there are provisional measures which appear as proprio motu together with the dispute with no need for a judicial decision. In this article, the provisional measure based on UNCLOS and other agreements will be examined; then proprio motu provisional measures will be mentioned and finally way in which the ITLOS prescribes, modifies and revokes the provisional measures will be examined. Thereby, a comprehensive framework of jurisdiction for provisional measure of ITLOS will have been set out.
Jurisdiction of the International Tribunal for the Law of the Sea for Provisional Measures